A Christian Islamist?. Issue 6 (1st January 2013) - Qadhi, Yasir
Abstract: In this review, the author discusses Volf's paradigm from an Islamic perspective, and compares and contrasts some of Volf's assertions with those of his avowed counterpart: the Muslim fundamentalist Syed Qutb. Some interesting questions are raised, and the differences between these two paradigms, it is claimed, is not as great as what might initially appear.